Broadband directional filter in multilayer liquid crystal polymer films at W-band - Wang, Mengfa; Wang, Yiming; Qian, Jun; Li, Zhaolin; Xue, Wenhui; Qi, Victor; Zhang, Xijian; Ling, Haotian; Tang, Gongbin; Wang, Qingpu; Song, Aimin; Cao, Chao; et al. (Frontiers in Photonics, 2024)
In this work, a four-port directional filter (DF) with broad passband and low reflection is proposed at W-band, which comprises three unit filters at 92, 95, and 97 GHz cascaded in-series. Each unit consists of two microstrip lines in the top circuit layer for signal input and output, two pairs of apertures in the middle ground layer for directional coupling, and one square loop in the bottom layer as a selective resonator. By sweeping the working frequencies of the three units and optimizing the phase delays between them, the proposed filter achieves a 3-dB bandwidth of as broad as 16%, an insertion loss of 2.5 dB at 95 GHz, and an out-of-band rejection of -28 and -23 dB at 80 and 110 GHz, respectively. The corresponding reflection attenuation is larger than 9.6 dB from 60 to 105 GHz. To verify our design, a prototype is fabricated and characterized, and its experimental data are consistent with the simulation. This work significantly expands the bandwidth of DFs and may find many applications in frequency division multiplexing and high-gain wireless systems.